Penelitian Pengolahan Air Limbah Industri Tapioka - Aida Soelaeman; Susmirah Suryandari; siti Agustina; Endang Suriadi (Balai Besar Kimia dan Kemasan, 2000)
Waste water of tapioca industry come from cassava washing, extraction and sedimentation of starch The waste water normally has low pH, high COD, suspended solid and CN content The research has been done by using anaerob and aerob treatment and resulting that COD is decreasing up Lo 90%, pH = 7, suspended solid and CN content below than waste water quality standard, so the effluent can be discharge Lo the public rivers.